D-amino acid oxidase, D-serine and the dopamine system: their interactions and implications for schizophrenia - Betts, J (2012)
D-amino acid oxidase (DAO) is a flavin-dependent enzyme that is expressed in the mammalian brain. It is the metabolising enzyme of several D-amino acids, including D serine, which is an endogenous agonist at the glycine co-agonist site of the glutamatergic NMDA receptor. As such, regulation of D serine levels in the brain by DAO may indirectly modulate the activity of NMDA receptors. The expression and activity of DAO have been reported to be increased in schizophrenia. It has been identified as a putative susceptibility gene for the disorder, and as a potential therapeutic target. This thesis explored three aspects of the interface between DAO and the DA system. First, the expression of DA was investigated in the ventral tegmental area (VTA), the source of the dopaminergic mesocortical pathway. Traditionally, DAO was considered to be an enzyme confined to the hindbrain and to glia, but more recent studies have reported its expression in additional brain regions, and also in neurons. DAO mRNA and protein was found to be expressed in the VTA, and was present in both neurons and glia in this region, whereas in the cerebellum, DAO expression appeared solely glial. DA output from the VTA is regulated by NMDA receptors, and hence expression of DAO in the VTA suggests that it may serve a role in modulating cortical DA via regulation of D serine levels and NMDA receptor function. The second part of this thesis investigated the effects of DAO inhibition and D serine administration on DA levels in the prefrontal cortex (PFC) using in vivo microdialysis. Systemic DAO inhibition and D serine administration resulted in increases in extracellular levels of DA metabolites in the PFC, despite no detectable change in DA. Similarly, DA metabolites in the PFC increased after local application of D serine to the VTA, but no change was detected in DA. However, local DAO inhibition in the VTA resulted in increased levels of both DA and its metabolites, and DAO inhibition combined with D serine administration also produced increases in DA. This suggested that DAO and its regulation of D-serine levels may serve to indirectly modulate mesocortical DA function, and this may be mediated via the VTA. This notion was supported in the final section of this thesis, in which the expression of three DA genes was measured in the PFC of a novel line of DAO knockout mice. In this pilot study, there was evidence for an increase in Comt and Drd2 mRNAs in the knockout mice. As such, constitutive abolition of DAO activity may also alter mesocortical DA function. These studies provide new insights into the presence and role of DAO beyond the hindbrain, and point to a potentially important physiological function in modulating the activity of the mesocortical DA system via the VTA. This could be therapeutically relevant in the context of elevating cortical DA in the treatment of schizophrenia, and may provide supporting evidence for the clinical use of DAO inhibitors.